Characterization of a Xenopus laevis mitochondrial protein with a high affinity for supercoiled DNA. - Mignotte, B (1986)
A DNA binding protein of 31 Kd -mtDBPC- has been isolated from X. laevis oocyte mitochondria. It is present in large amounts in the organelle and does not show any enzymatic activity. Its binding to the superhelical form of a DNA is higher than for any other form, or for RNA. No sequence specificity could be found for any mtDNA fragments tested, including both origins of replication. It is able to introduce superhelical turns into relaxed circular DNA in the presence of a topoisomerase I activity. It could be a component of the mitochondrial nucleoids.